Sharing of experience from a collaborative program leader / Leow Min Hui - Leow, Min Hui (Academy of Language Studies, 2025)
A collaborative program, the Chinese Character Writing Competition, was held from the 28th to the 30th of October, with the closing ceremony taking place on the 9th of November 2024. The program was initiated by the lecturers from the Academy of Language Studies (APB). Universiti Teknologi MARA Cowangan Pulau Pinang (UiTMCPP), in collaboration with Universiti Kuala Lumpur - Malaysian Spanish Institute (UniKL MSI). As the program leader. I, Dr. Leow Min Hui, have gained valuable experience from leading and conducting the program. Thus, the significant insights from the program are worth sharing.